Influence of Water Temperature on Mist Spray Effectiveness for Thermal Comfort in Semi-Outdoor Spaces in Extremely Hot and Arid Climates - Ashraf Mohamed Soliman; Dilshan Remaz Ossen; Abbas Alwarafi; Amir Goli (Buildings)
The escalating summer heat in the Middle East and Northern Africa (MENA) region, particularly in Bahrain, poses a significant threat to human health, prompting the use of water mist systems for immediate heat stress relief and heat stroke treatment. Although these systems are known for their rapid cooling effects, the impact of varying water temperatures on their efficiency is not well understood. This research addressed this gap by investigating the effects of different water temperatures on cooling performance and user comfort in a semi-outdoor environment in Bahrain. Field experiments, comparing mist fan system (MFS) zones with non-misted areas, were conducted alongside user surveys to assess perceived thermal comfort. The findings revealed that lower water temperatures significantly enhanced cooling, with a 7.7 °C water temperature achieving a 4 °C temperature reduction and improving perceived comfort. The MFS effectively shifted participant perceptions from “Hot” or “Slightly Warm” to “Natural” or “Slightly Cool”, confirming its rapid heat mitigation capabilities. Notably, 54.5% of participants preferred the system using the coldest water, citing immediate relief. Despite the substantial cooling benefits, achieving standard thermal comfort during peak heat remained challenging. Future research should explore nozzle optimization, wind effects, water usage, solar-powered system efficiency, and the impact of clothing on thermal comfort.